Associations of neighborhood racial and ethnic, economical, and educational segregation with breast cancer risk: The Multiethnic ohort Study - Ugonna Ihenacho; Jenna Khan-Gates; Katherine Lin; Janine V. Abe; Pushkar P. Inamdar; Juan Yang; Yuqing Li; Meera Sangaramoorthy; Christopher A. Haiman; Loïc Le Marchand; Lynne R. Wilkens; Scarlett Lin Gomez; et al. (Cancer Causes & Control, 2026)
Purpose Residential segregation is recognized as an upstream driver of poor health, yet few studies have evaluated its impact on breast cancer incidence at a local level. We examined associations of neighborhood residential segregation with breast cancer (BC) incidence in the Multiethnic Cohort Study (MEC). Methods Measures of Index of Concentration at the Extremes were developed to assess residential segregation by income, education, race and ethnicity, and racialized income. A prospective study (1993–1996 through December 2019) was conducted to examine associations of these measures and breast cancer incidence for 101,785 African American, Japanese American, Latina, Native Hawaiian, and White female participants in the MEC, aged 45–75 years at baseline and residing in California and Hawai‘i. Multivariable Cox regression was conducted to evaluate the associations of several residential segregation measures with breast cancer incidence (cases = 7,381) adjusting for demographic, lifestyle, and reproductive factors. Results In California, BC risk was higher for females residing in neighborhoods with the highest compared to lowest concentration of privilege by income segregation (quintile 5 [Q5] vs. Q1: hazard ratio [HR] 1.12, 95% confidence interval [CI] 1.00–1.25, P trend = 0.001) and education segregation (Q5 vs. Q1: HR 1.15, 95% CI 1.01–1.31; P trend = 0.01). For Latina females, risks increased with increasing privilege for measures of income, education, race and ethnicity, and racialized income residential segregation ( P trends < 0.05). No associations were observed in Hawai‘i. Conclusion In California, residential economic privilege was independently associated with increased BC risk. Future studies should examine neighborhood- and individual-level pathways placing females residing in privileged areas at greater risk.